2009
DOI: 10.1007/s00296-009-1080-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between disease activity and depression in patients with Behcet disease and rheumatoid arthritis

Abstract: Disease activity may be questioned as a possible related factor to depression in patients with rheumatoid arthritis (RA) and Behcet disease (BD). Our aims were to determine and compare the depression levels of patients with RA and BD and to investigate a possible association between disease activity and depression scores of the patients. A total of 30 RA and 30 BD patients were included in this study. In RA patients; pain, morning stiffness duration, systemic involvement, tender-swollen joints, the physician-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…Melikoglu et al found positive correlations between BDS and arthralgia and patient's impression of disease activity subgroups of BDCAF. 30 To our knowledge, this is the first study to demonstrate a significant association between depression and all components of BDCAF.…”
Section: Discussionmentioning
confidence: 70%
“…Melikoglu et al found positive correlations between BDS and arthralgia and patient's impression of disease activity subgroups of BDCAF. 30 To our knowledge, this is the first study to demonstrate a significant association between depression and all components of BDCAF.…”
Section: Discussionmentioning
confidence: 70%
“…They found that levels of anxiety and depressive symptoms were higher in BS subjects with fibromyalgia than in those without this comorbidity. Moreover, there are numerous data from observational studies regarding evaluation of depression by means of the BDI and evaluation of anxiety by means of the BAI, which have confirmed a higher prevalence of these disorders in BS patients than in patients with other autoimmune disorders, such as rheumatoid arthritis and psoriasis [46,47].…”
Section: Behçet's Syndrome Anxiety and Mood Disordersmentioning
confidence: 97%
“…We agree that, unfortunately, research on depression screening and management is lacking. Our article was a comprehensive literature review identifying multiple studies that demonstrated that the prevalence of depression in patients with psoriatic disease and RA was higher compared with control groups 9,10,11,12,13,14,15,16,17 . A published metaanalysis that helped corroborate our finding reported an overall depression prevalence of 28% in PsO and that patients with PsO were more likely to have depression than those without PsO (OR 1.57, 95% CI 1.40-1.76) 18 .…”
Section: To the Editormentioning
confidence: 99%